The Effect of Store Atmosphere, Store Image and Servicescape on Purchase Decisions at Gramedia Padang Book Store - Abaharis, Henryanto; Afifa, Devi (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of the influence of Store Atmosphere, Store Image and Servicescape on Purchase Decisions at Gramedia Padang Bookstores. This research is quantitative research, the sampling method using accidental sampling technique with the number of respondents 100 people. The data analysis technique used in this study was multiple regression analysis. The results of this study indicate that Store Atmosphere has a positive and significant effect on purchasing decisions, Store Image has a positive and significant effect on purchasing decisions, and Servicescape has a positive and significant effect on purchasing decisions